Investigation of three-dimensional bacterial adhesion manner on model organic surfaces using quartz crystal microbalance with energy dissipation monitoring - Latag, Glenn Villena (2023)
Bacterial biofilms reduce the performance and efficiency of biomedical and industrial devices. The initial step in forming bacterial biofilms is the weak and reversible attachment of the bacterial cells onto the surface. This is followed by bond maturation and secretion of polymeric substances, which initiate irreversible biofilm formation, resulting in stable biofilms. This implies that understanding the initial reversible stage of the adhesion process is crucial to prevent bacterial biofilm formation. In this study, we analyzed the adhesion processes of E. coli on self-assembled monolayers (SAMs) with different terminal groups using optical microscopy and quartz crystal microbalance with energy dissipation (QCM-D) monitoring. We found that a considerable number of bacterial cells adhere to hydrophobic (methyl-terminated) and hydrophilic protein-adsorbing (amine- and carboxy-terminated) SAMs forming dense bacterial adlayers while attaching weakly to hydrophilic protein-resisting SAMs [oligo(ethylene glycol) (OEG) and sulfobetaine (SB)], forming sparse but dissipative bacterial adlayers. Moreover, we observed positive shifts in the resonant frequency for the hydrophilic protein-resisting SAMs at high overtone numbers, suggesting how bacterial cells cling to the surface using their appendages as explained by the coupled-resonator model. By exploiting the differences in the acoustic wave penetration depths at each overtone, we estimated the distance of the bacterial cell body from different surfaces. The estimated distances provide a possible explanation for why bacterial cells tend to attach firmly to some surfaces and weakly to others. This result is correlated to the strength of the bacterium-substratum bonds at the interface. Elucidating how the bacterial cells adhere to different surface chemistries can be a suitable guide in identifying surfaces with a more significant probability of contamination by bacterial biofilms and designing bacteria-resistant surfaces and coatings with excellent bacterial antifouling characteristics.